2019
DOI: 10.1371/journal.pone.0218722
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and associated factors among pregnant women attending antenatal care service in Debre Markos town health facilities, Northwest Ethiopia

Abstract: Background Intimate partner violence is a thoughtful public health concern and human rights violation towards pregnant women for it has a significant negative health effect on the life of both the mother and her fetus. However, there is a scanty of information about the extent of intimate partner violence during pregnancy in Ethiopia, particularly in the study area. Therefore, the current study was conducted to determine the prevalence of intimate partner violence among pregnant women attending an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
67
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 33 publications
(36 reference statements)
28
67
2
5
Order By: Relevance
“…This finding is similar to the previous study conducted in Gondar Hospital, which reported a prevalence of sexual IPV of 2.4% [42]. However, a higher prevalence of sexual IPV among pregnant women was reported by other studies from Ethiopia that were conducted in Jimma (30%) [16], Debre-Berhan (19.8%) [17], Hulet Ejju Enessie district (14.8%) [43], and Bale Zone (36.3%) [18]. The low prevalence of sexual IPV in the current study might be attributed to women's strong disapproval of sexual violence as more than 99% of women in this study believed that women had the right to refuse sex.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is similar to the previous study conducted in Gondar Hospital, which reported a prevalence of sexual IPV of 2.4% [42]. However, a higher prevalence of sexual IPV among pregnant women was reported by other studies from Ethiopia that were conducted in Jimma (30%) [16], Debre-Berhan (19.8%) [17], Hulet Ejju Enessie district (14.8%) [43], and Bale Zone (36.3%) [18]. The low prevalence of sexual IPV in the current study might be attributed to women's strong disapproval of sexual violence as more than 99% of women in this study believed that women had the right to refuse sex.…”
Section: Discussionsupporting
confidence: 89%
“…A previous Ethiopian study indicated that women who considered that dowry had an impact on the way she was treated by her husband and his family were more likely to experience IPV during pregnancy than those who considered it had no impact on the way she was treated [16]. Other researchers from Ethiopia also reported associations between IPV during pregnancy and a woman and her partner being uneducated [19], early marriage, partner's alcohol consumption [14], chewing khat, [13], and rural residency [17]. Other factors that have been found to have an association with IPV include controlling behaviour by the partner [28], duration of marriage [29], and engaging in polygamous relationships [30].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed women whose husbands attained primary and secondary education are more likely to disclose their experience as compared to those who attain more than secondary education [21,22]. It might be because women, a wife of an educated man, are more likely to keep a secret, to keep his dignity to the level expected by society as an educated, respected, and well-conducted man.…”
mentioning
confidence: 60%
“…The highest prevalence was found among female sex workers (31.9%) (95% CI 26.7, 37.1) [71] in Nigeria, followed by a study in Ghana (24.6%) (95% CI 20.5, 29.2) [98]. Correspondingly, a study conducted in Ethiopia showed one in five pregnant women experienced IPV over the past year [52].…”
Section: Prevalence Of Emotional Ipv Among Women Aged 15-49 Years Of Agementioning
confidence: 99%